5-Fluoro-2-(4-fluorophenyl)-7-methyl-3-phenylsulfinyl-1-benzofuran - Seo, Pil Ja (International Union of Crystallography, 2013)
In the title compound, C(21)H(14)F(2)O(2)S, the dihedral angles between the mean plane [r.m.s. deviation = 0.007 (2) Å] of the benzofuran ring system and the pendant 4-fluorophenyl and phenyl rings are 5.93 (9) and 80.23 (5)°, respectively. In the crystal, molecules are linked by weak C—H⋯O and C—H⋯π interactions, forming a three-dimensional network.